Cost-effectiveness of Total Knee Arthroplasty in the United States: Patient Risk and Hospital Volume - Losina, Elena (2009)
BACKGROUND: Total knee arthroplasty (TKA) relieves pain and improves quality of life for persons with advanced knee osteoarthritis. However, to our knowledge, the cost-effectiveness of TKA and the influences of hospital volume and patient risk on TKA cost-effectiveness have not been investigated in the United States. METHODS: We developed a Markov, state-transition, computer simulation model and populated it with Medicare claims data and cost and outcomes data from national and multinational sources. We projected lifetime costs and quality-adjusted life expectancy (QALE) for different risk populations and varied TKA intervention and hospital volume. Cost-effectiveness of TKA was estimated across all patient risk and hospital volume permutations. Finally, we conducted sensitivity analyses to determine various parameters’ influences on cost-effectiveness. RESULTS: Overall, TKA increased QALE from 6.822 to 7.957 quality-adjusted life years (QALYs). Lifetime costs rose from $37 100 (no TKA) to $57 900 after TKA, resulting in an incremental cost-effectiveness ratio of $18 300 per QALY. For high-risk patients, TKA increased QALE from 5.713 to 6.594 QALY, yielding a cost-effectiveness ratio of $28 100 per QALY. At all risk levels, TKA was more costly and less effective in low-volume centers than in high-volume centers. Results were insensitive to variations of key input parameters within policy-relevant, clinically plausible ranges. The greatest variations were seen for the quality of life gain after TKA and the cost of TKA. CONCLUSIONS: Total knee arthroplasty appears to be cost-effective in the US Medicare-aged population, as currently practiced across all risk groups. Policy decisions should be made on the basis of available local options for TKA. However, when a high-volume hospital is available, TKAs performed in a high-volume hospital confer even greater value per dollar spent than TKAs performed in low-volume centers.